Self-assembled Co–BaZrO3 nanocomposite thin films with ultra-fine vertically aligned Co nanopillars. Issue 23 (2nd June 2017) - Huang, Jijie; Li, Leigang; Lu, Ping; Qi, Zhimin; Sun, Xing; Zhang, Xinghang; Wang, Haiyan
Abstract : A simple one-step pulsed laser deposition (PLD) method has been applied to grow self-assembled metal–oxide nanocomposite thin films. Abstract : A simple one-step pulsed laser deposition (PLD) method has been applied to grow self-assembled metal–oxide nanocomposite thin films. The as-deposited Co–BaZrO3 films show high epitaxial quality with ultra-fine vertically aligned Co nanopillars (diameter <5 nm) embedded in a BZO matrix. The diameter of the nanopillars can be further tuned by varying the deposition frequency. The metal and oxide phases grow separately without inter-diffusion or mixing. Taking advantage of this unique structure, a high saturation magnetization of ∼1375 emu cm −3 in the Co-BaZrO3 nanocomposites has been achieved and further confirmed by Lorentz microscopy imaging in TEM. Furthermore, the coercivity values of this nanocomposite thin films range from 600 Oe (20 Hz) to 1020 Oe (2 Hz), which makes the nanocomposite an ideal candidate for high-density perpendicular recording media.